Study on facilities in orphanage homes / Zati Nur Diyana Che Shopi - Che Shopi, Zati Nur Diyana (Faculty of Architecture, Planning and Surveying, 2010)
An orphanage home is a residential institution devoted to the care and education of orphans. Orphan homes provide an alternative to foster care or adoption by giving orphans a community-based setting in which they live and learn. Many of orphanage homes are not properly well managed and lack of facilities and equipments. Most of homes have a low level of effectiveness in facilities. The objectives of the study is to identify requirement of facilities provided in the building based on guideline by Jabatan Kebajikan Masyarakat, Malaysia and Jabatan Kerajaan Tempatan and to identify user satisfaction in orphanage homes and to give recommendation regarding on the research a study on facilities in orphanage homes. The source of the study was used primary and secondary data. The instrument use in conducting a survey is questionnaire to staffs and residents, facilities audit and interviews. From the analysis, mostly staffs and residents stated they are not satisfied with the facilities, equipments, insufficient things and poor environment at the house. The enforcement should be implemented before the orphan homes can be established, refer a guideline by overseas or welfare department in organising an orphan homes.